Curve Benders - Nour, David (Ascent Audio, 2021)
A personal growth roadmap guiding you into the future of relationships in work, life, play, and giving Curve Benders is a personal growth roadmap. It will guide you through the complicated intersection of work, life, play, and giving. Countless new forces will shape the future, so the strategic relationships we form in these areas of life are, of necessity, changing. This book will show you how to move into the future and dramatically alter your growth trajectory in both its direction and ultimate destination. David Nour, the author of Relationship Economics and a top thought leader on business relationships, has identified fifteen forces that will heavily influence what we do and how and where we engage our current and prospective relationships to create value and make a difference in the lives of others. This book aims to provide you with a step-by-step guide for personal, professional, and organizational growth. The author highlights how certain relationships enable a non-linear growth trajectory. These relationships, in addition to augmenting what we can accomplish, often shape who we become. These relationships are "curve benders," and this book will show you who and where they are, how to find and engage them, and, equally valuable, how you can become a curve bender to impact the lives and livelihoods of others profoundly.
Online resource; Title from title page (viewed May 25, 2021)
Keywords: Audiobooks; Livres audio